Three-dimensional Modeling of the Interaction of a Bubble pair with a Rigid Wall using Boundary Integral Method - Imad A. Aziz (Zanco Journal of Pure and Applied Sciences, 2024)
This study examines the three-dimensional dynamics of two gas bubbles near a horizontal rigid wall, focusing on how inter-bubble distance affects their shape, size, and jet formation. The Boundary Integral Method (BIM) with a novel local smoothing technique is employed. Critical parameters including jet velocity, bubble centroid movement, bubble radius, and collapse time are computed for each bubble to understand their interaction dynamics comprehensively. The velocity vector field and pressure distribution surrounding the bubbles are analyzed, providing detailed insights into the fluid dynamics. The findings demonstrate that inter-bubble distance significantly influences their interaction and overall behavior. These results advance the understanding of bubble dynamics near rigid boundaries, with potential applications across various scientific and engineering disciplines.